EMPLOYEE PERFORMANCE IN MICRO BANKING AND SEVERAL FACTORS THAT INCREASE IT - Alfato Yusnar Kharismasyah; Yudhistira Pradhipta Aryoko (Universitas Muhammadiyah Metro Lampung, 2022)
The purpose of this research was to analyze and explain the effect of the work environment, work ethos, work discipline and organizational citizenship behavior on the performance of employees of PT BPR BKK Purwokerto (Perseroda). This research was a quantitative research using a questionnaire of 167 respondents to employees of PT BPR BKK Purwokerto branch (Perseroda). The ampling technique used nonprobability sampling method and the Slovin formula. Data analysis used validity test, reliability test, classic assumption test, multiple inear regression test, determination coefficient test, t test and f test. The results of his research show that work environment had a positive and significant effect on employee performance, work ethic had a positive and significant effect on employee performance, work discipline had a positive and significant effect on employee performance, organizational citizenship behavior had a positive and significant effect on employee performance and significantly Simultaneous work environment, work ethos, work discipline and organizational citizenship behavior have a positive and significant effect on employee performance.Keywords: work environment, work ethos, work discipline, organizational citizenship behavior, employee performance.